Distribution and assessment of heavy metals in suspended particles in the Sundarban mangrove river, Bangladesh. (August 2022) - Zou, Xiaochun; Li, Yunhai; Wang, Liang; Ahmed, Mohammad Kawser; Chen, Keliang; Wu, Jianwei; Xu, Yonghang; Lin, Yunpeng; Xiao, Xianbiao; Chen, Baohong; Wu, Kankan; Liu, Jinwen; et al.
Abstract: The suspended particulate matter (SPM) is an important carrier of heavy metals transportation from land to sea, so it is significant to study the heavy metal pollution in SPM. The distribution and assessment of five heavy metals (Mn, Cr, Ni, Cu, and Pb) in SPM collected from Passur River and its estuary in Sundarban were studied in combination with water temperature, salinity, and turbidity. The results show that the heavy metal content and distribution in SPM are mainly controlled by runoff input, hydrodynamic process and the interaction process of salt and fresh water in estuaries. The quality evaluation results of heavy metals in SPM show that pollution degree is light. Studies on the heavy metals in SPM are of great significance to comprehensively evaluate regional pollution status and carry out early warning. Graphical abstract: Unlabelled Image Highlights: Suspended particulate matter is the carrier of heavy metal transport. Hydrodynamics and estuarine processes control the distribution of heavy metals. Heavy metals in suspended particulate matter were evaluated.